Prenova slovenskega stanovanjskega sklada v luči evropskih prostorskih omrežij - Zupančič-Strojan, Tadeja (Urbani izziv, 2004)
Following analyses of development prospects offered by trends in supra-regional material and im-material communication, recollection about issues in renewal of the Slovene housing stock is becoming a very dynamic dimension. The polarised space of traditional, authentic identity and space of multiple, rapidly changing variety is beginning to reach the limits of its dimension and is calling for renewed search for balance. Similar observations apply to the polar concept of centres and peripheral areas that feed the former, whatever the physical scale of discussion. Our contribution therefore deals with the search for dynamic balance between inevitable globalisation processes and survival of local space. Conscious balancing of extreme trends and respect for multiple, not necessarily economic or nature conservation dimensions of sustainability, but also wider cultural ones in any physical scale, can help in establishing dynamic balance. Comparison between results of two goal-oriented national research-development programmes points out that Slovenian physical planning policies stands before a responsible task, which is, how to balance development trends, not only on the national and regional, but also sub-regional, and above all the local level.
Keywords: arhitekturni prostor; infrastructure; infrastruktura; prenova; prostor; prostorski razvoj; prostorsko planiranje; spatial planning; stanovanja; stanovanjska naselja; urbana sociologija